2012
DOI: 10.1051/0004-6361/201118062
|View full text |Cite
|
Sign up to set email alerts
|

Low-resolution spectroscopy of the Sunyaev-Zel’dovich effect and estimates of cluster parameters

Abstract: Context. The Sunyaev-Zel'dovich (SZ) effect is a powerful tool for studying clusters of galaxies and cosmology. Large mm-wave telescopes are now routinely detecting and mapping the SZ effect in a number of clusters, measure their comptonisation parameter and use them as probes of the large-scale structure and evolution of the universe. Aims. We show that estimates of the physical parameters of clusters (optical depth, plasma temperature, peculiar velocity, non-thermal components etc.) obtained from ground-base… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 31 publications
0
33
0
Order By: Relevance
“…8 we plot a simulation of a 3-hours observation of the Sunyaev-Zeldovich (SZ) effect in a typical cluster of galaxies, obtained using a room-temperature differ- ential MPI on a stratospheric balloon (like the OLIMPO experiment [15]), with photon-noise limited TES detectors working in bands optimized as described above. See [16] for details. The potential of this method is evident, despite of the bandwidth limitation due to the emissivity of the WGs discussed here.…”
Section: Resultsmentioning
confidence: 99%
“…8 we plot a simulation of a 3-hours observation of the Sunyaev-Zeldovich (SZ) effect in a typical cluster of galaxies, obtained using a room-temperature differ- ential MPI on a stratospheric balloon (like the OLIMPO experiment [15]), with photon-noise limited TES detectors working in bands optimized as described above. See [16] for details. The potential of this method is evident, despite of the bandwidth limitation due to the emissivity of the WGs discussed here.…”
Section: Resultsmentioning
confidence: 99%
“…requires detailed spectral informations in the whole mm range. de Bernardis et al 26 have shown that a differential spectrometer covering four bands with a resolution of ∼ 6 GHz eliminates most of the bias resolution in a full recovery of the input cluster parameters. This possibility is clearly hampered in ground-based few-band photometers while spectrometers suitable for balloon borne observations or for dedicated space missions would make the necessary step forward.…”
Section: Spectrometric Measurements Of the Sz Effectmentioning
confidence: 99%
“…OLIMPO will be launched on June 2017 from Svalbard Islands and will represent the first possibility to explore the use of a FTS coupled with a four-band photometer in the millimetric and sub-millimetric range. Simulations 26 show that even a warm spectrometer, mounted on a balloon borne experiment like OLIMPO, 72 allows an unbiased recovery of the galaxy cluster thermal optical depth, electron temperature, dust contamination, non-thermal optical depth, despite being still limited at high frequencies by radiative background. A low earth-orbit satellite like SAGACE 27 improves the capability to detect non-thermal effects and the disentangling from foregrounds.…”
Section: Spectrometric Measurements Of the Sz Effectmentioning
confidence: 99%
“…The DFTS is intrinsically rejecting the large common mode signal from the telescope, the residual atmosphere and the CMB monopole. The effectiveness of this instrument in removing degeneracies between cluster (and foreground) parameters has been discussed in de Bernardis et al 2012. OLIMPO will carry-out an ambitious observation program, including spectroscopic observations of the SZ in 40 known clusters, plus a 10 • × 10 • blind deep-sky survey.…”
Section: Olimpomentioning
confidence: 99%